2014
DOI: 10.4161/nucl.36290
|View full text |Cite
|
Sign up to set email alerts
|

A novel cell permeable DNA replication and repair marker

Abstract: Proliferating Cell Nuclear Antigen (PCNA) is a key protein in DNA replication and repair. The dynamics of replication and repair in live cells is usually studied introducing translational fusions of PCNA. To obviate the need for transfection and bypass the problem of difficult to transfect and/or short lived cells, we have now developed a cell permeable replication and/or repair marker. The design of this marker has three essential molecular components: (1) an optimized artificial PCNA binding peptide; (2) a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 39 publications
(46 reference statements)
0
13
0
Order By: Relevance
“…To further support this conclusion, we stained HeLa cells for Arl13b as well as PCNA (proliferating cell nuclear antigen). PCNA is a DNA clamp that promotes polymerase δ interaction with DNA during the S-phase of the cell cycle to increase processivity (Herce et al, 2014). While PCNA is found in the nucleus at all stages of the cell cycle, it becomes concentrated and localized in foci of active DNA synthesis during S-phase forming a specific, punctate staining pattern within the nucleus (Herce et al 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further support this conclusion, we stained HeLa cells for Arl13b as well as PCNA (proliferating cell nuclear antigen). PCNA is a DNA clamp that promotes polymerase δ interaction with DNA during the S-phase of the cell cycle to increase processivity (Herce et al, 2014). While PCNA is found in the nucleus at all stages of the cell cycle, it becomes concentrated and localized in foci of active DNA synthesis during S-phase forming a specific, punctate staining pattern within the nucleus (Herce et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…PCNA is a DNA clamp that promotes polymerase δ interaction with DNA during the S-phase of the cell cycle to increase processivity (Herce et al, 2014). While PCNA is found in the nucleus at all stages of the cell cycle, it becomes concentrated and localized in foci of active DNA synthesis during S-phase forming a specific, punctate staining pattern within the nucleus (Herce et al 2014). As shown in Figure 2B, HeLa cells that exhibited the distinctive PCNA S-phase staining pattern (Figure 2B, depicted with arrow) in addition stained positive for Arl13b (Figure 2B, depicted with arrowhead), further suggesting the presence of primary cilia in cells that are in the S-Phase of the cell cycle.…”
Section: Resultsmentioning
confidence: 99%
“…Images of PCNA nuclear distribution can be used to differentiate the early, mid and late cell-cycle S phase [39]. Moreover, research on DNA replication and restoration in living cells can be enhanced by introducing PCNA translational fusions which would offer the excellent advantage of application in in situ living tissues, and it especially distinguishes between cells in the process of replication and cells undergoing repair [40]. One study also proved that PCNA is a potential therapeutic target in cancer therapy [41] and we confirmed that PCNA decreased in the EPB41L4A-AS2 over-expressing group.…”
Section: Discussionmentioning
confidence: 99%
“…The histological analysis conducted in the present study showed the positive effect of FAA and DP diets on white muscle morphology, more precisely, on the diameter of white muscles and the number of the PCNA positive myonuclei, which reflect the ability of muscle cells to proliferate. It was confirmed that the PCNA protein indicated the replication or repair processes of myonuclei [31]. Similarly, common carp feeding with feeds based on WG supplemented with free Lys and Gly amino acids had a beneficial effect on the proliferation of muscle cells, whereas fish feeding the WG-based diet supplemented with Lys-Gly dipeptide stimulated the development of muscle tissue by the increase of TFN [14].…”
Section: Discussionmentioning
confidence: 78%